Environmental filters shaping angiosperm tree assembly along climatic and geographic gradients. (17th June 2018) - Kubota, Yasuhiro; Kusumoto, Buntarou; Shiono, Takayuki; Ulrich, Werner
Abstract: Question: Global‐scale forest censuses provide an opportunity to understand diversification processes in woody plant communities. Based on the climatic or geographic filtering hypotheses associated with tropical niche conservatism and dispersal limitation, we analysed phylogenetic community structures across a wide range of biomes and evaluated to what extent region‐specific processes have influenced large‐scale diversity patterns of tree species communities across latitude or continent. Location: Global. Methods: We generated a data set of species abundances for 21, 379 angiosperm woody plants in 843 plots worldwide. We calculated net relatedness index (NRI) for each plot, based on a single global species pool and regional species pools, and phylogenetic β‐diversity (PBD) between plots. Then, we explored the correlations of NRI with climatic and geographic variables, and clarified phylogenetic dissimilarity along geographic and climatic differences. We also compared these patterns for South America, Africa, the Indo‐Pacific, Australia, the Nearctic, Western Palearctic and Eastern Palearctic. Results: NRI based on a global‐scale species pool was negatively associated with precipitation and positively associated with Quaternary temperature change. PBD was positively associated with geographic distance and precipitation difference between plots across tropical and extratropical biomes. Moreover, phylogenetic dissimilarity was smaller in extratropical regions than in regions including the tropics, although temperate forests of the Eastern Palearctic showed a greater dissimilarity within extratropical regions. Conclusions: Our findings support predictions of the climatic and geographic filtering hypotheses. Climatic filtering (climatic harshness and paleoclimatic change) relative to tropical niche conservatism played a role in sorting species from the global species pool and shaped the large‐scale diversity patterns, such as the latitudinal gradient observed across continents. Geographic filtering associated with dispersal limitation substantially contributed to regional divergence of tropical/extratropical biomes among continents. Old, long‐standing geographic barriers and recent climatic events differently influenced evolutionary diversification of angiosperm tree communities in tropical and extratropical biomes. Abstract : Forest dynamics plots across a wide range of biomes provide an opportunity to understand diversification processes in woody plant communities from an evolutionary perspective. Geographic pattern of phylogenetic dissimilarity of angiosperm tree communities revealed that long‐standing geographic barriers, Quaternary climatic change, and current climatic harshness differently acted as environmental filters for evolutionary diversification in tropical and extratropical biomes.